Studies on the Virucidal Effects of UV-C of 233 nm and 275 nm Wavelengths - Jessica Kohs; Tom Lichtenthäler; Carolyn Gouma; Hyun Kyong Cho; Andreas Reith; Axel Kramer; Sven Reiche; Paula Zwicker (Viruses)
Among the physical decontamination methods, treatment with ultraviolet (UV) radiation is a suitable means of preventing viral infections. Mercury vapor lamps (254 nm) used for room decontamination are potentially damaging to human skin (radiation) and harmful to the environment (mercury). Therefore, other UV-C wavelengths (100–280 nm) may be effective for virus inactivation on skin without damaging it, e.g., far-UV-C radiation with a wavelength of 233 nm, which is absorbed in the outer layer of the skin and thus does not reach the deeper layers of the skin. For room disinfection, 275 nm UV-C LED lamps could be a more environmentally friendly alternative, since toxic mercury is avoided. A carrier test using multiple viruses was used to determine the TCID50/mL value on stainless steel, PVC, and glass carriers. In addition to the inactivation kinetics (233 nm), the necessary UV-C dose for 4 lg inactivation (275 nm) was investigated. The impact of irradiance on the inactivation efficacy was also assessed. The inactivation of the viruses was a function of the radiation dose. UV-C-radiation at 233 nm (80 mJ/cm2) inactivated from 1.49 ± 0.08 to 4.28 ± 0.18 lg depending on the virus used. To achieve a 4 lg inactivation (275 nm) for enveloped viruses, doses of up to 70 mJ/cm2 (SuHV-1) were sufficient. For non-enveloped viruses, a maximum dose of 600 mJ/cm2 (MS2) was necessary. Enveloped viruses were inactivated with lower doses compared to non-enveloped viruses. Higher radiation doses were required for inactivation at 275 nm in comparison to 254 nm. A more environmentally friendly alternative to mercury vapor lamps is available with 275 nm LED emitters. Radiation at 233 nm could serve as an additional prophylactic or therapeutic measure for virus inactivation in direct contact with human skin.